Review of the bee genus Pseudoanthidium Friese, 1898 (Hymenoptera: Apoidea: Megachilidae: Anthidiini) of China with descriptions of three new species - Niu, Ze-Qing; Luo, A-Rong; Griswold, Terry; Zhu, Chao-Dong (Zootaxa, 2021)
The carder bee genus Pseudoanthidium Friese, 1898, is revised from China. Eight species are confirmed to occur in China, including three new species: Pseudoanthidium (Pseudoanthidium) yanruae Niu & Zhu, sp. nov., P. (P.) kunesense Niu & Zhu, sp. nov., P. (P.) chenggongense Niu & Zhu, sp. nov. There is also one new generic assignment and synonymy: Anthidium kryzhanovskii Wu, 1962 is a junior synonym of P. (P.) orientale (Bingham, 1897). Pseudoanthidium (P.) campulodonta (Wu, 1990) is synonymized with P. (P.) tenellum (Mocsáry, 1880). Here we provide descriptions for the three new species and an illustrated key to the known Chinese Pseudoanthidium.